Estudo comparativo de microabrasão no aço inoxidável austenítico ISO 5832-1: solubilizado, nitretado por plasma em baixa temperatura e processado via SHTPN - Tonella Junior, Jorge Luiz (2017)
The following research evaluated the possibility of an application's increase of austentic stainless steel in environments that demand high wear resistance through two different nitrogen surface enrichment methods. On this research were used authentic stainless steel ISO 5832-1 samples, treated by Plasma Nitriding (PN) and Solution Heat Treatment after Plasma Nitriding - SHTPN, being evaluated the wear resistance through micro abrasion test. The evaluation parameters of wear were: Wear depthness, wear volume and wear coefficient.It was noted that the SHTPN process tends to ensure a long life cycle on situations involving wear of authentic stainless steel ISO 5832-1, when compared to the PN method, thus increasing the applications of austentic steel.